A balanced secure cryptographic algorithm against timing and side channel attacks - Abu, Nur Azman; Abd Ghafar, Amir Hamzah (Institute for Mathematical Research, Universiti Putra Malaysia, 2014)
Historically, a computing resource is scarce and expensive. In the last few decades, considerable efforts have been made to design efficient codes in terms of the storage space and running time. Due to the progress on computing resources and cost of memory, an efficient algorithm has ironically become a threat to cryptographic operations. An efficient unbalanced code opens another room for timing and side channel attacks on the private key of public key infrastructure (PKI). This paper shall highlight and propose balanced secure algorithms for cryptographic operations to avoid feasible timing and side channel attacks in the immediate future.